2018
DOI: 10.1051/matecconf/201815005095
|View full text |Cite
|
Sign up to set email alerts
|

The Discussion of Social Entrepreneurship: Review of the Literature

Abstract: The purpose of this article is to explore the various discussion of social entrepreneurship. Social entrepreneurship provides a unique opportunity and assumptions to question, challenge and rethink from different perspective of management and business research. This article offers a comparative analysis of commercial entrepreneurship and social entrepreneurship using a prevailing analytical model from commercial entrepreneurship. The analysis highlights key differences and similarities between commercial entre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Previous research on social entrepreneurship in educational institutions at the Institute of Teacher Education in Malaysia encouraged academics and education practitioners to improve social entrepreneurship in educational practice (Daud et al, 2018). This study also found results that social entrepreneurship is a process of combining resources in new ways to create social value.…”
Section: Introductionmentioning
confidence: 54%
“…Previous research on social entrepreneurship in educational institutions at the Institute of Teacher Education in Malaysia encouraged academics and education practitioners to improve social entrepreneurship in educational practice (Daud et al, 2018). This study also found results that social entrepreneurship is a process of combining resources in new ways to create social value.…”
Section: Introductionmentioning
confidence: 54%
“…The social remittance is in the form of understanding technology and having an improved knowledge of the benefits of technology. Social remittance received during employment abroad has an important role in developing social entrepreneurship after the migrant workers return to their hometowns (18). From tables 1 and 3, it could be concluded that the second and third departure of the migrant workers had a tendency of an income increase.…”
Section: The Development Of Women Migrant Workers In Wonosobo Regencymentioning
confidence: 96%
“…Also, individuals who have a strong need to achieve are among those who want to solve problems themselves, set targets and strive for those targets through their efforts (Amin et al, 2018). The need for achievement has been extensively referenced in the literature and has commonly been demonstrated to be the key to entrepreneurial success (Amin et al, 2018;Fhiri et al, 2018;García & Capitán, 2021;Jumbri et al, 2019). This is because it has been observed that the need for achievement has a high correlation with entrepreneurship engagement.…”
Section: Mcclelland's Theory Of Needmentioning
confidence: 99%